Respuesta :

Answer: x = -4

               y = 2

Step-by-step explanation:

From equation I

-6x + 5y = 34

-6x = 34-5y

-(-6x) = -(34-5y)

or, 6x = 5y-34

or, x = 5y-34/6

so

substituting the value in equation II

-6x-10y = 4

or, -6{(5y-34)/6} - 10y = 4

or, -(5y-34)-10y = 4

or, -5y + 34-10y = 4

or, -15y = -30

or, y = -30/(-15)

so, y = 30/15

so, y = 2

now

x = (5y-34)/6

   = (5*2-34)/6

   = (10-34)/6

     = -24/6

     = -4

Answer:

x=-4, y=2

Step-by-step explanation:

-6x-10y=4

-6x=4+10y

(4+10y)+5y=34

15y=30

y=2

-6x-10(2)=4

-6x=24

x=-4